Novel soluble guanylyl cyclase activators increase glomerular cGMP, induce vasodilation and improve blood flow in the murine kidney. (3rd July 2021) - Stehle, Daniel; Xu, Min Ze; Schomber, Tibor; Hahn, Michael G.; Schweda, Frank; Feil, Susanne; Kraehling, Jan R.; Eitner, Frank; Patzak, Andreas; Sandner, Peter; Feil, Robert; Bénardeau, Agnès
Abstract : Background and Purpose: Generation of cGMP via NO‐sensitive soluble guanylyl cyclase (sGC) has been implicated in the regulation of renal functions. Chronic kidney disease (CKD) is associated with decreased NO bioavailability, increased oxidative stress and oxidation of sGC to its haem‐free form, apo‐sGC. Apo‐sGC cannot be activated by NO, resulting in impaired cGMP signalling that is associated with chronic kidney disease progression. We hypothesised that sGC activators, which activate apo‐sGC independently of NO, increase renal cGMP production under conditions of oxidative stress, thereby improving renal blood flow (RBF) and kidney function. Experimental Approach: Two novel sGC activators, runcaciguat and BAY‐543, were tested on murine kidney. We measured cGMP levels in real time in kidney slices of cGMP sensor mice, vasodilation of pre‐constricted glomerular arterioles and RBF in isolated perfused kidneys. Experiments were performed at baseline conditions, under L‐NAME‐induced NO deficiency, and in the presence of oxidative stress induced by ODQ. Key Results: Mouse glomeruli showed NO‐induced cGMP increases. Under baseline conditions, sGC activator did not alter glomerular cGMP concentration or NO‐induced cGMP generation. In the presence of ODQ, NO‐induced glomerular cGMP signals were markedly reduced, whereas sGC activator induced strong cGMP increases. L‐NAME and ODQ pretreated isolated glomerular arterioles were strongly dilated by sGC activator. sGC activator also increased cGMP and RBF in ODQ‐perfused kidneys. Conclusion and Implication: sGC activators increase glomerular cGMP, dilate glomerular arterioles and improve RBF under disease‐relevant oxidative stress conditions. Therefore, sGC activators represent a promising class of drugs for chronic kidney disease treatment. LINKED ARTICLES: This article is part of a themed issue on cGMP Signalling in Cell Growth and Survival. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.11/issuetoc Abstract :